2008
DOI: 10.1590/s1415-54192008000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da resistência ao cisalhamento do compósito Right-On em diferentes condições de esmalte

Abstract: OBJETIVO: avaliar a resistência ao cisalhamento da união de braquetes metálicos colados com o compósito Right-On, em diferentes condições de superfície. MATERIAL E MÉTODOS: foram utilizados 45 incisivos inferiores permanentes bovinos divididos em três grupos (n = 15). No grupo 1 (controle), as colagens foram realizadas com Transbond XT seguindo as recomendações do fabricante, ou seja condicionamento com ácido fosfórico a 37%, lavagem, secagem, aplicação de XT primer e colagem propriamente dita. Nos outros dois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
6
3
1
Order By: Relevance
“…Groups 3 and 4, using Orthoprimer/Orthobond adhesive system obtained, respectively, 12.76 MPa and 13.01 MPa. This average was also higher than previous researches 3 . These great extent are explained by variations of 3.5 MPa to 27.8 MPa found 5 , and due to different methodology used in the SBS test studies, such as: the position of the knife-edge rod in the bracket 24 , storage time after bonding 25,26 , bracket base area 2 , adhesive polymerization time, and the crosshead speed of the test 5 .…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Groups 3 and 4, using Orthoprimer/Orthobond adhesive system obtained, respectively, 12.76 MPa and 13.01 MPa. This average was also higher than previous researches 3 . These great extent are explained by variations of 3.5 MPa to 27.8 MPa found 5 , and due to different methodology used in the SBS test studies, such as: the position of the knife-edge rod in the bracket 24 , storage time after bonding 25,26 , bracket base area 2 , adhesive polymerization time, and the crosshead speed of the test 5 .…”
Section: Discussioncontrasting
confidence: 74%
“…Significant differences were found in this study between SBS of the adhesive systems of healthy groups 1 and 3, as previously reported by Pithon et al 3 (2008), and between eroded groups 2 and 4. However, in spite of these statistical differences found, both adhesive systems obtained SBS compatible to clinical use, higher than the average strength -6 MPa to 8 MPa, recommended by literature 2,3 . The prevalence of the ARI score 2, over 50% adhesive on enamel, was found in this study, mainly for groups 3 and 4, with lower SBS values, nevertheless no statistical differences were found between the tested groups, in accordance with other studies 21,24,27 .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, our results confront studies which reported the majority of disruptions in the interface composite/ bracket. 4,15,16,19,24 After shear bond strength test and during the ARI evaluation enamel fractures were observed in four specimens distributed among the four groups. This relative frequency of fractures among groups, supported by the study by Liu et al, 10 may be associated with high strength supported by the samples.…”
Section: Resultsmentioning
confidence: 99%
“…tubes (Tigre) with 25 mm of diameter / 25 mm of height, filled with special plaster stone (Durone -Dentsply). 16 In the moment of the teeth insertion, the buccal surfaces were positioned perpendicular to the ground, using as an aid a juxtaposed square to the bonding surface and the excesses were removed with a spatula LeCron (Duflex). The specimens were stored again at 0.9 % saline solution.…”
Section: Methodsmentioning
confidence: 99%